(untitled) (Hoboken, N.J., 2007)
This respected series is designed to help the chemistry community keep current with the many new developments in computational techniques. Volume 6 examines quantum chemistry of solvated molecules, molecular mechanics of inorganics and organometallics, modeling of polymers, technology of massively parallel computing, and productivity of molecular modeling software. A guide to force field parameters and a compendium of computational chemistry software are included to provide background information.
Keywords: Chemistry,Chemistry,Hóa học,Hóa học; Data processing,Mathematics,Xử lý dữ liệu,Toán học